(untitled) (American Journal of Islam and Society, 2019)
Muna Ali’s Young Muslim America is a multi-layered, multi-disciplinary work that delivers a snapshot of American Muslim life, grounded in history and theory. She begins by saying she is looking at individual narratives embedded in a larger narrative “about being and belonging, about identity politics in a globalizing world where grand narratives of national and civilizational histories, secularism, and global wars are summoned” (4). The idea of “narrative” is repeated because it signals a primary methodological approach of the book, where narratives are seen as full of information used to navigate social realities (5).